2023
DOI: 10.3389/fpsyg.2023.1020269
|View full text |Cite
|
Sign up to set email alerts
|

Relationships among students’ reading habits, study skills, and academic achievement in English at the secondary level

Abstract: IntroductionReading is an attempt to comprehend the writer’s message for personal growth and success in the relevant fields. Thus, psychologists consider it a multifaceted cognitive process of constructing meanings from texts. The present study was conducted to determine the relationships among students’ reading habits, study skills, and academic achievement in English at the secondary level in Punjab, Pakistan.MethodsThe (n = 1614) students enrolled in the science section for the academic year 2019–2020 parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 68 publications
(108 reference statements)
1
9
0
3
Order By: Relevance
“…Abid and Akhtar [33] found a gender influence on students' variables such as engagement, interpersonal skills, study skills. Moreover, Abid et al [34] found that reading habits influence on academic achievement through study skills.…”
Section: Discussionmentioning
confidence: 99%
“…Abid and Akhtar [33] found a gender influence on students' variables such as engagement, interpersonal skills, study skills. Moreover, Abid et al [34] found that reading habits influence on academic achievement through study skills.…”
Section: Discussionmentioning
confidence: 99%
“…Azmi et al (2022) in a study, it was found that the majority of the students had traumatic experience on virtual learning during COVID lockdowns and close to 75% of the surveyed students had suffered from stress and fear of examination. In a study by Abid et al (2023) of the relation between the reading habit and the academic performance of the students in the secondary level, it was found that there was a strong correlation between these two. The role of teachers and academic planners in incorporating library timetables into the curriculum and ensuring their effective implementation was thoroughly examined.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Lalu pada indikator ketiga yaitu books read (bacaan yang telah dibaca), skor rata-rata yang didapatkan adalah sebesar 3,60 (sangat tinggi). Temuan ini menggambarkan bahwa pembaca tidak hanya mengeksplorasi banyak judul komik, tetapi juga memberikan perhatian khusus pada kualitas isi komik yang mereka nikmati, yang menjadi salah satu faktor penting untuk meningkatkan kebiasaan membaca (Abid et al, 2023). Tabel 11 menjelaskan hasil analisis data dari enam indikator variabel dependen (kemampuan critical reading) yang diadopsi dari teori critical thinking Facione (2013), dimana hasilnya masing-masing indikator memiliki skor berbeda.…”
Section: No Kebiasaan Membacaunclassified